New genetic resources in wheat breeding for an increased grain protein content - O. P. Mitrofanova; A. G. Khakimova (Вавиловский журнал генетики и селекции)
The present review offers an overview of genetic research on grain protein content (GPC) in various Triticum L. and Aegilops L. species. Regularities in geographic variability of GPC and the results of a longterm screening of accessions from the VIR collection for this trait are considered. On the basis of these assessments, a core-collection of genetic sources with high GPC has been formed. It includes the diploid Aegilops species as donors of B, G and D genomes for allopolyploid wheats, as well as accessions of di-, tetra- and hexaploid wheat species. The use of highprotein sources in wheat breeding in the United States and Canada in the 1970’s–1980’s resulted in the bread wheat GPC increase by 0.5–3.0 %; however, further purposeful attempts at increasing GPC by traditional breeding methods failed. A breakthrough in increasing the total GPC has been achieved as a result of molecular genetics methods and molecular markers development. For the first time, a functional locus, or the Gpc-B1 gene (chromosome 6BS) affecting the accumulation of protein, Zn and Fe in grain, was identified in T. dicoccoides, cloned and studied in detail. The application of molecular markers has revealed the active allele of this gene in some landraces and old cul-tivars of T. dicoccum, T. durum, T. spelta and T. aestivum. Moreover, Gpc-A1, Gpc-D1, and Gpc-2 wheat genes have been found in chromosomes 6A, 6D and homeologous group 2, respectively. All these genes have been identified as NAC transcription factors, which play an important role in the accelerated senescence of plants and remobilization of nutrients from leaves to grain. The genes related to Gpc-B1 from T. dicoccoides were found in the G genome of T. timopheevii and B (=S) genome of different species of Aegilops sect. sitopsis. Functional Gpc-B1 alleles have been introduced into commercial tetra- and hexaploid wheat cultivars, and it resulted in the creation of new highprotein and high-yield cultivars and series of nearly isogenic lines in different countries. They are promising sources for research and wheat breeding purposes.